2019
DOI: 10.3390/genes10060472
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analyses of the Chitinases under Cold and Osmotic Stress in Ammopiptanthus nanus

Abstract: Chitinase is a kind of hydrolase with chitin as a substrate and is proposed to play an essential role in plant defense system by functioning against fungal pathogens through degrading chitin. Recent studies indicated chitinase is also involved in abiotic stress response in plants, helping plants to survive in stressful environments. A. nanus, a rare evergreen broad-leaved shrub distrusted in deserts in Central Asia, exhibits a high level of tolerance to drought and low temperature stresses. To identify the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…The phylogenetic analysis of the 31 chitinase sequences was carried out using the neighbor-joining method ( Figure 1 ), and five types of chitinase proteins were identified, which was consistent with the previous Ammopiptanthus nanus chitinases [ 37 ]. The mulberry chitinase genes were divided into two large branches: one was composed of Classes I, II and IV, and the other was composed of Classes III and V.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The phylogenetic analysis of the 31 chitinase sequences was carried out using the neighbor-joining method ( Figure 1 ), and five types of chitinase proteins were identified, which was consistent with the previous Ammopiptanthus nanus chitinases [ 37 ]. The mulberry chitinase genes were divided into two large branches: one was composed of Classes I, II and IV, and the other was composed of Classes III and V.…”
Section: Resultssupporting
confidence: 81%
“…We identified a chitinase gene family in M. notabilis ( Table 1 and Figure 1 ), for which a total of 26 mulberry chitinase genes were identified. Compared with the number of chitinase genes in other plants, mulberry is relatively small, but more than Arabidopsis [ 37 ]. This indicates that during the evolution process, the chitinase genes of mulberry have not been significantly amplified.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean roots, the α/β-hydrolase superfamily proteins Glyma06g44990 and Glyma12g12800 were increased in response to flooding stress, after a 2-day flooding treatment [50]. The Xylanase inhibitor protein gene encodes the Glyco_hydro_18 domain-containing protein that is involved in osmotic and low temperature stress responses in plants, helping them to survive in stressful environments [51]. The highly up-regulated Serine carboxypeptidase-like protein gene OsBISCPL1 has a similar domain in rice and was reported to be involved in regulation of defense responses against pathogen infection and oxidative stress [52].…”
Section: Waterlogging Stress Up-regulated Genes Related To Response Tmentioning
confidence: 99%
“…It is a relatively small group, but it is present in highly consumed fruits [75]. Chitinases can be divided into five classes (I-V), and plant class III chitinases (PR-8 proteins) have an additional lysozyme activity, which is not found in other classes of chitinases [76]. Marzban et al [33] identified four allergen proteins including class III chitinase in raspberry fruits.…”
Section: Chitinase III As Allergen In Raspberrymentioning
confidence: 99%